Some New Medicinal Properties of Neem - a Multipurpose Farm Forestry Tree - Aggarwal, S. K.; Dhawan, V. K. (Indian Forester, 1995)
Neem is a very valuable multipurpose farm forestry tree. After chemical analysis its constituents have been of immense medicinal value other than their commonly known uses.